Titis Istiqomah ANALISIS STRATEJIK REVITALISASI MANAJEMEN SUMBER DAYA LESTARI (STUDI PERANAN WANITA DI PESISIR KABUPATEN SIDOARJO): Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *e-mail: pdklpi@gmail.com - Titis Istiqomah (GREENOMIKA, 2019)
Coastal women are still widely regarded as marginal figures within the scope of economic empowerment and the application of science and technology. The personal and psychological superiority of women as contributors who play a role in processing capture fisheries products is basically a real strength and opportunity in order to create processed products that are competitive and sustainable. The research objective was to find a strategy for implementing revitalization of sustainable resource management through increasing the role of coastal women. The research is descriptive; conducted in several capture fisheries centers in Sidoarjo Regency such as: Banjar Kemuning, Gisik Cemandi, Segoro Tambak, Bluru Kidul and Tanjung Sari during 2015. The method used is terrestrial survey combined with inventory activities, marine side interviews, home in near fishing ports interviews were assisted by a questionnaire that contained a list of indepth questions. The data is processed using fish bone diagram analysis which is given a weight based on the assumptions prepared using the Balance Score Cards method. The results of the subsequent analysis are compiled into several basic assumptions which are further analyzed using the SWOT matrix. The results of the study show that the principle of implementation of gender equality has been established in various coastal areas in East Java. The implementation of equality in various regions is only differentiated by the level of participation, where coastal women in Banjar Kemuning and Gisik Cemandi have a participation rate of up to 73.2% and 69.4%. While the participation rates in Segoro Tambak, Bluru Kidul and Tanjung Sari were 43.6%, 61.1% and 57.8% respectively. The level of women's contribution to the competitiveness of the products produced is measured by productivity, the sustainability of the processing business and the added value obtained shows that the average has reached more than 57%. The magnitude of the figure shows that the level of participation and contribution of coastal women still needs to be increased. Based on the results of the SWOT analysis, it was found that the strategy to implement the contribution of coastal women to create competitiveness of processed fishery products that need to be developed is to introduce continuous global market dynamics (score 170), train / familiarize the application of quality systems in fish processing early (score 130) ; and provide a more innovative discourse on product diversification (110).